Production and Cytophysiology Applications of 3-hydroxyalkanoic Acid Monomers - X.H. Zou (Chemical Engineering Transactions, 2015)
Polyhydroxyalkanoates (PHAs) have been developed for use as polymeric materials to make bioplastics, fine chemicals, implant biomaterials, medicine, and biofuels. PHAs are produced by microorganisms grown under restricted conditions and they are comprised of structurally diverse monomers. Various 3-hydroxyalkanoic acids (3-HA) can be prepared by chemical synthesis, as well as by depolymerizing PHAs and microbial metabolic engineering. PHAs derived from 3-HA monomers are compatible with alcohol and carboxylic acids due to their easily modified hydroxyl and carboxyl functional groups. Therefore, an important application for 3 - HA monomers is as a starting material for fine chemical synthesis, such as production of antibiotics, vitamins, aromatics and pheromones. 3-HA also has different physiological uses such and as such can be used for drug manufacture. Here, we focus on the production of 3-HA monomers, their relationship with the promotion of cell proliferation inhibition of apoptosis and suppression of oxidative and nitrosative stress. These discussions will provide a foundation for understanding the properties of 3-HA to optimize their applications in cytophysiology.